The Influence of Students' Worksheet Types in the Implementation of Experimental Method toward the Students' Physics Learning Outcomes at the Tenth Grade of SMA Negeri 9 Makassar (Jurnal Pendidikan Fisika, 2019)
The research a quasi-experiment which aimed to determine difference in physics learning out come between the students were the thought by experimental method with experimental LKPD and the students were thought by using experimental method with constructivism. Based LKPD on temperature and heat lesson. The research design was used intac group comparison design. The independent variable in this research was using experimental method accompanied by experimental LKPD and accompanying by constructivism-based LKPD while the dependent variable was the result of learning physics students. The subject of research were students of tenth grade of nine state senior high school of Makassar in the even semester on 2017/2018 academic year with 174 students AND 63 students was as sample and each 30 students was as control class and 33 experimental classes were determined by the principle. The research hypothesis, there were significant differences about the physics learning result of students who were taught by using the intermediate experimental method accompanied by experimental LKPD and accompanying by constructivism-based LKPD. The research instrumental was used the test of physics learning outcomes that valid criteria with reliability 0,0902 with 30 items. Descriptive analysis result showed that average score of students taught using experimental method accompanied by experimental LKPD were 15,57 with a standard deviation 3,51, while the average score of students taught using experimental method with constructivism-based LKPD was 14,53, with a standard deviation 3,02 from inferential analysis the hypothesis test used Test- t with a significant level of α = 0,05 obtained thitung  = 4, 792and ttable  = 1,999, based on  the testing criteria for values if thitung > t or 4, 792 > 1,999 , there was significant differences in physics students who was taught using the experimental method were accompanied by constructivism-based LKPD at the 95% confidence level..Keywords: Experimental Method, Experimental LKPD, LKPD Based on Constructivism, Physics Learning OutcomesPenelitian ini adalah eksperimen semu yang bertujuan untuk mengetahui perbedaan hasil belajar fisika antara peserta didik yang diajar menggunakan metode eksperimen disertai LKPD eksperimen dengan peserta didik yang diajar menggunakan metode eksperimen disertai LKPD berbasis konstruktivisme pada materi suhu dan kalor. Desain yang digunakan pada penelitian ini adalah Intac Group Comparison Design. Variabel bebas dalam penelitian ini adalah pembelajaran menggunakan metode eksperimen disertai LKPD eksperimen dan disertai LKPD berbasis konstruktivisme. Sedangkan variabel terikatnyanya adalah hasil belajar fisika peserta didik. Subjek populasi penelitian ini adalah peserta didik kelas X SMA Negeri 9 Makassar pada semester genap tahun ajaran 2017/2018 sebanyak 174 peserta didik dan sampel sebanyak 63 peserta didik yang masing-masing 30 peserta didik kelas kontrol dan 33 kelas eksperimen yang ditentukan oleh pihak sekolah. Hipotesis penelitian adalah terdapat perbedaan  yang signifikan tentang hasil belajar fisika peserta didik yang diajar menggunakan metode eksperimen antara yang disertai LKPD eksperimen dan yang disertai LKPD berbasis konstruktivisme. Instrumen penelitian yang digunakan adalah tes hasil belajar fisika yang memenuhi kriteria valid dengan reliabilitas soal 0,902 sebanyak 30 butir. Hasil analisis deskriptif menunjukkan bahwa skor rata-rata peserta didik yang diajar menggunakan metode eksperimen disertai LKPD eksperimen adalah 15,57 dengan standar deviasi 3,51, sedangkan skor rata-rata peserta didik yang diajar menggunakan metode eksperimen disertai LKPD berbasis konstruktivisme adalah 14,53 dengan standar deviasi 3,02. Dari analisis inferensial uji hipotesis menggunakan uji-t dengan taraf signifikan α = 0,05 diperoleh thitung= 4,792 dan ttabel= 1,999, berdasarkan criteria pengujian terhadap nilai t yaitu jika thitung> ttabel atau 4,792 > 1,999 maka terdapat perbedaan yang signifikan tentang hasil belajar fisika peserta didik yang diajar menggunakan metode eksperimen antara yang disertai LKPD eksperimen dan yang disertai LKPD berbasis konstruktivisme pada taraf kepercayaan 95 %.Kata kunci: Metode Eksperimen, LKPD Eksperimen, LKPD berbasis Konstruktivisme, Hasil Belajar  Fisika